(untitled) (American Journal of Islam and Society, 2002)
In their book Jewish Fundamentalism in Israel, Shahak and Mezvinsky document the nature of Jewish fundamentalism and argue that it is a growing threat to Israeli society. As a work of activist scholarship, the authors point out that their aim is not to present new scholarship but to document, in English, literature that is normally available only in Hebrew, and to make the links between Jewish fundamentalism and Israeli politics clearer. As such, this is a fascinating, informative, and easy-to-read book for anyone interested in Israeli politics, Judaism, and its relation to Israeli policies toward Palestine. It presents facets of Orthodox Judaism (particularly messianic, which they consider most dangerous) and Israeli politics not usually available to those without access to Hebrew sow·ces. Shahak and Mezvinsky show that Judaism, like any other religion or ideology, has its extremists and fundamentalists and that these views have very real effects on state politics and public opinion. In fact, they take a stance few are willing to risk: describing Israeli intolerance of non-Jews as Jewish Nazism. Each chapter discus9es in meticulous- at times, excessive- detail the history and characteristics of particular religious groups and parties in Israel. The authors quote throughout from a diverse range of sources, from religious texts and rabbinical writings to news articles in such Israeli dailies as Ha’aretz. In the preface, the authors lay out the book’s context: "We have written this book in order to reveal the essential character of Jewish fundamentalism and its adherents. This character threatens democratic features of Israeli society." They add, furthermore: "We believe that a critique of Jewish fundamentalism, which entails a critique of the Jewish past, can help Jews acquire more understanding and improve their behavior toward Palestinians." At this point, their aim is linked primarily to prospects for peace in the Middle East, though by the end of the book their concern seems more focused on Israel itself. At the end of chapter 7, they state: ...